Preclinical evaluation of 18F-PSMA-1007, a new prostate-specific membrane antigen ligand for prostate cancer imaging - Cardinale, Jens; Leotta, Karin; Haberkorn, Uwe; Giesel, Frederik L. (Journal of nuclear medicine, 2017)
In recent years, several radiotracers targeting the prostate-specific membrane antigen (PSMA) have been introduced. Some of them have had a high clinical impact on the treatment of patients with prostate cancer. However, the number of 18F-labeled tracers addressing PSMA is still limited. Therefore, we aimed to develop a radiofluorinated molecule resembling the structure of therapeutic PSMA-617. Methods: The nonradioactive reference compound PSMA-1007 and the precursor were produced by solid-phase chemistry. The radioligand 18F-PSMA-1007 was produced by a 2-step procedure with the prosthetic group 6-18F-fluoronicotinic acid 2,3,5,6-tetrafluorophenyl ester. The binding affinity of the ligand for PSMA and its internalization properties were evaluated in vitro with PSMA-positive LNCaP (lymph node carcinoma of the prostate) cells. Further, organ distribution studies were performed with mice bearing LNCaP and PC-3 (prostate cancer cell line; PSMA-negative) tumors. Finally, small-animal PET imaging of an LNCaP tumor-bearing mouse was performed. Results: The identified ligand had a binding affinity of 6.7 ± 1.7 nM for PSMA and an exceptionally high internalization ratio (67% ± 13%) in vitro. In organ distribution studies, high and specific tumor uptake (8.0 ± 2.4 percentage injected dose per gram) in LNCaP tumor-bearing mice was observed. In the small-animal PET experiments, LNCaP tumors were clearly visualized. Conclusion: The radiofluorinated PSMA ligand showed promising characteristics in its preclinical evaluation, and the feasibility of prostate cancer imaging was demonstrated by small-animal PET studies. Therefore, we recommend clinical transfer of the radioligand 18F-PSMA-1007 for use as a diagnostic PET tracer in prestaging and monitoring of prostate cancer.